(3QjGVjGJ GdJehjd h GdGSJKeGQ (B/s - (3GHh HcQ, YjO GMeOs ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
1) (3GdaGFOI GdHSjWI (B: (3GdaGFOI h GdLedI, GdbjeI GdMGdjI h GdNUe , NUe GdGhQGb GdJLGQjI , SOGO h JShjI GdOjhf bUjQI GdGLd , GdOaYGJ , WQb SOGO (B((3GSJgdGc(B) (3GdbQhV bUjQI GdGLd (B2) (3GdaGFOI GdeQcHI (B: (3GdaGFOI h GdLedI , GdbjeI GdMGdjI h GdNUe , JShjI h GSJHOGd GdOjhf WhjdI GdGLd , GdOaYGJ GdeJSGhjI , GSJgdGc GdbQhV GdYGOjI , Jbjje h GSJgdGc GdSfOGJ (B.s
(3eQGLY U(B.543 (3;LOGhd U(B.503s
Keywords: (3GdEMUGA GdQjGVjs; (3GdESJKeGQs; (3GdJehjds; (3GdQjGVjGJ(B- (3GdeGdjIs